A Zebrafish Model for a Human Myopathy Associated with Mutation of the Unconventional Myosin MYO18B. Issue 2 (1st February 2017) - Gurung, Ritika; Ono, Yosuke; Baxendale, Sarah; Lee, Samantha Lin Chiou; Moore, Steven; Calvert, Meredith; Ingham, Philip W
Abstract: Myosin 18B is an unconventional myosin that has been implicated in tumor progression in humans. In addition, loss-of-function mutations of the MYO18B gene have recently been identified in several patients exhibiting symptoms of nemaline myopathy. In mouse, mutation of Myo18B results in early developmental arrest associated with cardiomyopathy, precluding analysis of its effects on skeletal muscle development. The zebrafish, frozen ( fro ) mutant was identified as one of a group of immotile mutants in the 1996 Tübingen genetic screen. Mutant embryos display a loss of birefringency in their skeletal muscle, indicative of disrupted sarcomeric organization. Using meiotic mapping, we localized the fro locus to the previously unannotated zebrafish myo18b gene, the product of which shares close to 50% identity with its human ortholog. Transcription of myo18b is restricted to fast-twitch myocytes in the zebrafish embryo; consistent with this, fro mutant embryos exhibit defects specifically in their fast-twitch skeletal muscles. We show that sarcomeric assembly is blocked at an early stage in fro mutants, leading to the disorganized accumulation of actin, myosin, and α-actinin and a complete loss of myofibrillar organization in fast-twitch muscles.